From the Law at the cross-roads to the Whole System of Norms -: Development of Medical Law with reference to Serbian Law - Mujović, Hajrija (Glasnik Advokatske komore Vojvodine, 2020)
The subject of this article is to clarify the role and specificity of Medical law as a scientific discipline and a particular area of ​​law. The aim is to investigate, through medico-legal settings, the broadening of the legal regulation of the field of performing medical activities in the protection of human health, which is the role of health legislation, with reference to the historical, developmental dimension, as well as to the character of sources of Medical law. In doing so, the issues of conceptual delineation and relation to other related fields, especially Health law, are a particular topic of consideration. In its beginning, Medical law was shaped by the merging of a large number of different branches of law: Human rights, Contract and Compensation law, Property law, Family law, Public law and Criminal law. Medical law was not autonomously studied in its subject, and today it is widely accepted in the field of Law studies. However, there is still some ignorance of this discipline, even among its supporters, as to what subject it involves and how it differs from other areas of law. Academic staff is looking for more space for this discipline. Analyzes of disputed medical cases, as well as the development of legal institutes and the practice of Medical law have become a subject of increasing attention in Serbian law over time. The conclusion is that the field of Medical law has undergone its explosive development and at the same time contributed to the full recognition of the rights of various categories of patients. In addition, the discipline of Medical law is gaining international prominence through the launch of increasingly topical global health topics and the collaboration of states and scientific communities on international Medical law.
Keywords: Law science, legal disciplines, Medical law, narrower and broader term, Health legislation